Minorities and storable votes - Casella, Alessandra; Palfrey, Thomas R. 1953-; Riezman, Raymond Glenn 1947- (CESifo Working paper, 2005)
The paper studies a simple voting system that has the potential to increase the power of minorities without sacrificing aggregate efficiency. Storable votes grant each voter a stock of votes to spend as desired over a series of binary decisions. By accumulating votes on issues that it deems most important, the minority can win occasionally. But because the majority typically can outvote it, the minority wins only if its strength of preference is high and the majority's strength of preference is low. The result is that with storable votes, aggregate efficiency either falls little or in fact rises. The theoretical predictions of our model are confirmed by a series of experiments: the frequency of minority victories, the relative payoff of the minority versus the majority, and the aggregate payoffs all match the theory.